Réponses

Meilleure réponse !
2014-03-31T18:25:32+02:00
Bonsoir

S = 49 - 25x² - 2(7 -5x)(2x +3)
S = 49 -25x² - 2( 14x +21 -10x²  -15x)
S = 19 -25x² - 28x - 42 - 20x² + 30x
S = -45x² +2x -23

pour x = 0 ⇒ -23

pour x = - 1/3 ⇒ - 45(-1/3)² + 2(-1/3) -23
                       ⇒ -45 ( 1/9) + (-2/3) -23
                       ⇒ - 45/9 -2/3 -23 ⇒ -45/9 - 6/9 - 207/9 ⇒  - 258/9 = - 86/3

pour x = √2 ⇒ -45(√2)² + 2√2 - 23
                   ⇒ - 90 + 2√2 -23 ⇒ - 113 + 2√2


R = 49 -25x² = (7 -5x)(7 +5x)

S = ( 7 -5x)(7 +5x) - 2( 7-5x)(2x+3)
= (7x -5)( 7x +5) - 2 (2x+3)
⇒(7x-5)(7x+5 -4x -6) ⇒ (7x -5)(3x -1)